Effect of Streptomycin-Penicillin and Gentamicin-Tylosin- Lincomycin-Spectinomycin on the Quality and Bacterial Load of Frozen-Thawed Semen of Surti Buffalo Bull - Nandan, Devki; Gaur, Mitesh; Sharma, Deepak; Pargi, Kalpesh; Ram, Vachna (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present study evaluated the effect of two different antibiotic combinations SP (streptomycin, penicillin) and GTLS (gentamicin,  tylosin, lincomycin and spectinomycin), as antibiotic regimens in TCFY (Tris-citric acid-fructose-yolk) semen extender on Surti buffalo  bull semen. A total of 12 ejaculates from 6 bulls were collected. After evaluation of the dilution rate, the fresh semen was divided into  three parts. Each part of the semen was extended upto 80 million spermatozoa/mL. One control group (part 1) was maintained with  no antibiotics, while antibiotic combination SP and GTLS was added into part 2 and part 3 at the concentration of streptomycin 1000  µg/mL, penicillin 1000 IU/mL (Treatment-1), and gentamicin 500 µg/mL, tylosin 100 µg/mL, lincomycin 300 µg/mL and spectinomycin  600 µg/mL (Treatment-2). Pre-freeze and post-thaw microbial load (CFU/mL) and sperm abnormalities were found to be significantly  (p
Keywords: Antibiotic combinations; Bacterial load; Buffalo semen; Cryopreservation; Semen Quality